(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: Malocclusion was and remains one of the most common problems which affects the psyche and social status of the individual, so the estimation of the malocclusion severity and needs a percentage of orthodontic treatment of Iraqi patients is the aim of this study. Method: A randomly selected 150 pairs of study models (48 male and 102 female) were involved in this study for patients attending an orthodontic clinic at College of Dentistry/ University of Baghdad seeking for treatment. The DAI scores were collected according to WHO guidelines directly from the study model with a digital caliper, score was calculated using the regression equation of 10 occlusal traits. The dental casts were classified into four groups to determine the treatment needs. SPSS software version 25 was used to analyze the results. Results: 8.7% of orthodontic treated patients were with normal or mild malocclusion (DAI?25) and did not need treatment, while 56% of them were handicapped and needed mandatory treatment. In between them, patients with definite and severe malocclusion were 18.7% and 16.6% respectively. Molar deviation (72.6%) represents a high prevalence rate among occlusal traits, while negative overjet (7.3%) is the least one. Conclusions: Not all patients who are treated in an orthodontic clinic are really in need, and it must be the implementation of treatment need index to determine the treatment priority for patients.